Kualitas udara disektor industri karung plastik - Arum Yuniari; M. Sri Wahyuni; C. Yuwono Sumasto (Majalah Kulit, Karet, dan Plastik, 1998)
Air pollution is generated by air pollutant in production. Raw materials used in the production of plastic corrugated sack are Polyethylene and Polypropylene. Polyethylene and Polypropylene yars are knitted to be various plastic knits such as plastic corrugated sacks. The result of this study shows that concentration of dust particles in processing area is 30 – 34 ugr/m3, and in finishing area is 38,6- 972 ugr/m3. The other gases such as Ox, SO2, H2S and NH3 are still low. The overage concentration of dust particle in ambient air is about 38,6 – 380 ugr/m3. However for parameter of Ox, SO2, H2S and NH3 seems stile low